Factors influencing employees job satisfaction in foreign banks’ data processing centres - Logeswathy, Selvaras (2022)
This research was conducted to determine the factors that influence employees job satisfaction in foreign banks’ data processing centres at Kuala Lumpur. 304 respondents from three prominent foreign banks’ data processing centres involved in this study. The results of the study indicated that promotion opportunities, compensation and benefits, relationship with immediate supervisor and working environment positively predict job satisfaction, while relationship with co-workers negatively influence the job satisfaction however, when all the five independent variables combined has strong positive significant relationship with employee job satisfaction. It was identified that promotion opportunity is the most influential variable of employee job satisfaction in selected foreign banks’ data processing centres. Thus, employers need to consider enhancing the promotion opportunities by take a personal interest in employees’ career goals, promote training and development of employees and rotate employee roles in order to increase employees’ job satisfaction.